Ligand-Based Design of Allosteric Retinoic Acid Receptor-Related Orphan Receptor γt (RORγt) Inverse Agonists - Meijer, Femke A.; Doveston, Richard G.; de Vries, Rens M. J. M.; Vos, Gael M.; Vos, Alex A. A.; Leysen, Seppe; Scheepstra, Marcel; Ottmann, Christian; Milroy, Lech-Gustav; Brunsveld, Luc (Journal of medicinal chemistry, 2020)
Retinoic acid receptor-related orphan receptor gamma t (ROR gamma t) is a nuclear receptor associated with the pathogenesis of autoimmune diseases. Allosteric inhibition of ROR gamma t is conceptually new, unique for this specific nuclear receptor, and offers advantages over traditional orthosteric inhibition. Here, we report a highly efficient in silico-guided approach that led to the discovery of novel allosteric ROR gamma t inverse agonists with a distinct isoxazole chemotype. The the most potent compound, 25 (FM26), displayed submicromolar inhibition in a coactivator recruitment assay and effectively reduced IL-17a mRNA production in EM cells, a marker of ROR gamma t activity. The projected allosteric mode of action of 25 was confirmed by biochemical experiments and cocrystallization with the ROR gamma t ligand binding domain. The isoxazole compounds have promising pharmacokinetic properties comparable to other allosteric ligands but with a more diverse chemotype. The efficient ligand-based design approach adopted demonstrates its versatility in generating chemical diversity for allosteric targeting of ROR gamma t.